16S–23S rRNA Gene Intergenic Spacer Region Variability Helps Resolve Closely Related Sphingomonads - Tokajian, Sima; Issa, Nahla; Salloum, Tamara; Ibrahim, Joe; Farah, Maya (Frontiers in Microbiology, 2016)
Sphingomonads comprise a physiologically versatile group many of which appear to be adapted to oligotrophic environments, but several also had features in their genomes indicative of host associations. In this study, the extent variability of the 16S-23S rDNA intergenic spacer (ITS) sequences of 14 ATCC reference sphingomonad strains and 23 isolates recovered from drinking water was investigated through PCR amplification and sequencing. Sequencing analysis of the 16S-23S rRNA gene ITS region revealed that the ITS sizes for all studied isolates varied between 415 to 849 bp, while their G+C content was 42.2 mol% to 57.9 mol%. Five distinct ITS types were identified: ITSnone (without tRNA genes), ITSAla(TGC), ITSAla (TGC)+Ile (GAT), ITSIle (GAT)+Ala (TGC) and ITS Ile (GAT)+Pseudo. All of the identified tRNAAla (TGC) molecules consisted of 73 bases, and all of the tRNAIle (GAT) molecules consisted of 74 bases. We also detected striking variability in the size of the ITS region among the various examined isolates. Highest variability was detected within the ITS-2.